Perbandingan Hasil Belajar Pendidikan Jasmani Secara Offline Dan Online Sebuah Penelitian Ex Post Facto di SMA Negeri 30 Banda Maluku, Maluku Tengah - Ariyanto, Andi; Rumahlewang, Emma; Solissa, Jonas (Prgram Studi Pendidikan Jasmani Kesehatan dan Rekreasi, FKIP Universitas Pattimura, 2022)
This study aims to determine the comparison of offline and online physical education learning outcomes in SMA Negeri 30 Banda Maluku Tengah students. The method used in this research is quantitative using an ex post facto approach. The population in this study were XI MIA-2 class students totalling 25 students. The sample used was all students of class XI MIA-2. The pre-requisite tests carried out are homogeneity test and data normality test, and testing is done by t-test. Based on the results of data processing, the results of the t-test comparison of offline and online physical education learning outcomes obtained a t-count of 2.85. While the t-table is 2.06. This means that t-count> t table (2.85> 2.06) then the alternative hypothesis (Ha) is accepted. So there is a significant comparison between offline and online physical education learning outcomes in SMA Negeri 30 Banda Maluku Tengah students. The existence of factors that can affect student learning outcomes, such as constraints on students who do not have smartphones or mobile phones to take part in online learning, causes a comparison of learning outcomes between offline and online learning.